Informational Influence in Organizations: An Integrated Approach to Knowledge Adoption - Sussman, Stephanie Watts; Siegal, Wendy Schneier (Information Systems Research, 2003)
This research investigates how knowledge workers are influenced to adopt the advice that they receive in mediated contexts. The research integrates the Technology Acceptance Model (Davis 1989) with dual-process models of informational influence (e.g., Petty and Cacioppo 1986, Chaiken and Eagly 1976) to build a theoretical model of information adoption. This model highlights the assessment of information usefulness as a mediator of the information adoption process. Importantly, the model draws on the dual-process models to make predictions about the antecedents of informational usefulness under different processing conditions. The model is investigated qualitatively first, using interviews of a sample of 40 consultants, and then quantitatively on another sample of 63 consultants from the same international consulting organization. Data reflect participants' perceptions of actual e-mails they received from colleagues consisting of advice or recommendations. Results support the model, suggesting that the process models used to understand information adoption can be generalized to the field of knowledge management, and that usefulness serves a mediating role between influence processes and information adoption. Organizational knowledge work is becoming increasingly global. This research offers a model for understanding knowledge transfer using computer-mediated communication.